PENGARUH DISIPLIN KERJA, KOMPENSASI, MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT YOGYAKARTAS MEGA GRAFIKA - Pratama, Dhiyan Nanda; Kurniawan, Ignatius Soni (STKIP Persada Khatulistiwa Sintang, 2023)
To achieve the stated organizational goals, it must be supported by human resources who have the necessary competencies. The success of a company depends on the performance of its workforce, therefore employee performance is very important. The aim of this research is to determine the influence of work discipline, compensation and work motivation on employee performance at PT Yogyakartas Mega Graphics, Yogyakarta City. This research is quantitative research. The sampling technique uses respondents from all members of the population or census, namely 50 employees of PT Yogyakartas Mega Graphics as respondents. Data collection method uses a questionnaire. Data is analyzed using multiple linear regression analysis. The measuring instrument uses a Likert scale with the test equipment using validity and reliability tests, while research hypothesis testing uses the t test and coefficient of determination. According to the study's findings, performance was significantly impacted by work motivation and discipline, but performance was not much impacted by pay. The research's findings suggest that it's critical for businesses to support employee success by providing them with the work discipline, pay, and motivation they require.